CGIAR Research Program on Grain Legumes and Dryland Cereals - Plan of Work and Budget 2019 - CGIAR Research Program on Grain Legumes and Dryland Cereals (CGIAR Research Program on Grain Legumes and Dryland Cereals, 2019)
The CGIAR Research Program on Grain Legumes and Dryland Cereals (GLDC) is an international consortium led by the International Crops Research Institute for the Semi-Arid Tropics (ICRISAT) and CGIAR implementing partners including the International Institute for Tropical Agriculture (IITA), International Center for Agricultural Research in the Dry Areas (ICARDA), World Agroforestry Centre (ICRAF), International Livestock Research Institute (ILRI), International Water Management Institute (IWMI), and Bioversity International. In addition to the CGIAR, GLDC is implemented by IRD and CIRAD from France and CSIRO from Australia, besides various NGOs, NARS, and private sector partners. This consortium strives to support beneficiaries in 13 priority countries in South Asia and sub-Saharan Africa with a mission of delivering improved rural livelihoods and nutrition by prioritizing demand-driven innovation to increase production and market opportunities along value chains.